Randomized clinical trial of extended versus single‐dose perioperative antibiotic prophylaxis for acute calculous cholecystitis. Issue 2 (25th January 2017) - Loozen, C. S.; Kortram, K.; Kornmann, V. N. N.; van Ramshorst, B.; Vlaminckx, B.; Knibbe, C. A. J.; Kelder, J. C.; Donkervoort, S. C.; Nieuwenhuijzen, G. A. P.; Ponten, J. E. H.; van Geloven, A. A. W.; van Duijvendijk, P.; et al.
Abstract: Background: Many patients who have surgery for acute cholecystitis receive postoperative antibiotic prophylaxis, with the intent to reduce infectious complications. There is, however, no evidence that extending antibiotics beyond a single perioperative dose is advantageous. This study aimed to determine the effect of extended antibiotic prophylaxis on infectious complications in patients with mild acute cholecystitis undergoing cholecystectomy. Methods: For this randomized controlled non‐inferiority trial, adult patients with mild acute calculous cholecystitis undergoing cholecystectomy at six major teaching hospitals in the Netherlands, between April 2012 and September 2014, were assessed for eligibility. Patients were randomized to either a single preoperative dose of cefazolin (2000 mg), or antibiotic prophylaxis for 3 days after surgery (intravenous cefuroxime 750 mg plus metronidazole 500 mg, three times daily), in addition to the single dose. The primary endpoint was rate of infectious complications within 30 days after operation. Results: In the intention‐to‐treat analysis, three of 77 patients (4 per cent) in the extended antibiotic group and three of 73 (4 per cent) in the standard prophylaxis group developed postoperative infectious complications (absolute difference 0·2 (95 per cent c.i. –8·2 to 8·9) per cent). Based on a margin of 5 per cent, non‐inferiority of standard prophylaxis compared with extended prophylaxis was not proven. Median length of hospital stay was 3 days in the extended antibiotic group and 1 day in the standard prophylaxis group. Conclusion: Standard single‐dose antibiotic prophylaxis did not lead to an increase in postoperative infectious complications in patients with mild acute cholecystitis undergoing cholecystectomy. Registration number: NTR3089 (www.trialregister.nl ). Abstract : Single dose sufficient